Constitution and Family in the United States - Anderson, Carl (Revue générale de droit, 1990)
Decisions of the United States Supreme Court beginning with Griswold v. Connecticut (1965) have transformed family law in the United States. By characterizing the right to marry as a fundamental constitutional right and procreative decision-making as both a fundamental liberty interest and privacy right, the Court has “deregulated” the institutions of marriage and family.During this same period the Court’s approach to legal questions involving the rights of non-marital cohabitating couples as well as individual procreative decision-making has tended to blur legal distinctions between the family based upon marriage and other living arrangements. The widespread adoption of mutual consent and/or marital breakdown as grounds for the dissolution of marriage in the United States has significantly altered the social dynamics of marriage and further reduces distinctions between marriage and other living arrangements.However, recent decisions by the Court in Hardwick, Michael H., and Webster point to a change of direction in the Court’s view of privacy which may signal a willingness to tolerate greater community involvement in establishing protective regulation of the institutions of marriage and the family based upon it. The Court also appears to be in the process of significantly narrowing the constitutionally recognized right of privacy when viewed as a zone of autonomous decision-making for the individual or non-marital couple.